2016
DOI: 10.15344/2456-446x/2016/106
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Associated Inferior Mesenteric Vein Thrombosis

Abstract: Inferior mesenteric vein thrombosis is a rare complication after laparoscopic procedures. We presented a case of a 55-year-old woman who suffered from abdominal pain for two days. She received laparoscopic left hemicolectomy for sigmoid colon cancer two weeks ago. Computed tomography scan revealed a thrombus of the inferior mesenteric vein. The patient was managed conservatively in hospital. Her condition improved gradually without further symptoms and she was discharged after two weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, it has been reported that MVT of larger distal portions such as portal veins is mediated by local factors, such as malignancy, inflammation and infection while isolated MVT thrombosis is most commonly related to a prothrombotic state that originate from the vena rectae 6–8. There are very few case reports on IMVT, which have revealed associations with diverticulitis, antiphospholipid syndrome, postoperative and SARS-CoV-2 infection without definitive description of pathophysiology 9–13…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that MVT of larger distal portions such as portal veins is mediated by local factors, such as malignancy, inflammation and infection while isolated MVT thrombosis is most commonly related to a prothrombotic state that originate from the vena rectae 6–8. There are very few case reports on IMVT, which have revealed associations with diverticulitis, antiphospholipid syndrome, postoperative and SARS-CoV-2 infection without definitive description of pathophysiology 9–13…”
Section: Discussionmentioning
confidence: 99%